2009
DOI: 10.1007/s00381-009-1042-0
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocartilaginous mesenchymoma of the spine in a child: a case report

Abstract: Given the rarity of spinal FCM, there are no guidelines about its management. However, treatment of this neoplasm seems to be mainly surgical aiming at total removal of the lesion, if feasible, as FCM may recur locally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 12 publications
0
20
0
3
Order By: Relevance
“…Our patient's other potential diagnosis, fibrocartilaginous mesenchymoma, is a benign locally aggressive bone tumor of children and adolescents; to the best of our knowledge, only twenty cases have been reported in the literature 1,4,5,8 . It was first described in 1984 when Dahlin et al reported five cases of a previously unrecognized bone neoplasm that was called fibrocartilaginous mesenchymoma with low-grade malignancy 4,5,15 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our patient's other potential diagnosis, fibrocartilaginous mesenchymoma, is a benign locally aggressive bone tumor of children and adolescents; to the best of our knowledge, only twenty cases have been reported in the literature 1,4,5,8 . It was first described in 1984 when Dahlin et al reported five cases of a previously unrecognized bone neoplasm that was called fibrocartilaginous mesenchymoma with low-grade malignancy 4,5,15 .…”
Section: Discussionmentioning
confidence: 83%
“…Radiographs demonstrated a predominantly osteolytic metaphyseal lesion with focal mineralization, which characterizes this lesion 1 . Intraoperative biopsy revealed a lesion with predominantly chondroid matrix, which was admixed with trabecular bone, and a bland-to-hypercellular fibrous stroma showing sparse polymorphism without mitotic figures, all of which are characteristic of this lesion; the diagnosis was supported by later confirmation of the GNAS mutation by polymerase chain reaction 6,8,9 . Described treatments for fibrocartilaginous dysplasia include observation, curettage with bone-grafting, intramedullary nailing, and en bloc excision 1,5,10-12 .…”
Section: Discussionmentioning
confidence: 86%
“…El diagnóstico diferencial incluye lesiones benignas, como el quiste óseo simple, quiste óseo aneurismático, histiocitosis, displasia fibrocartilaginosa (DFC), displasia fibrosa, fibroma desmoplásico, quiste óseo aneurismático, fibroma condromixoide, condroblastoma y tumor de células gigantes. 7,8,11 A l g u n a s l e s i o n e s m a l i g n a s , c o m o e l condrosarcoma, osteosarcoma de bajo grado, fibrosarcoma y sarcoma de Ewing, también deben ser consideradas. 4,11 El principal diagnóstico diferencial del mesenquimoma fibrocartilaginoso es la displasia fibrocartilaginosa.…”
Section: Discussionunclassified
“…7,8,11 A l g u n a s l e s i o n e s m a l i g n a s , c o m o e l condrosarcoma, osteosarcoma de bajo grado, fibrosarcoma y sarcoma de Ewing, también deben ser consideradas. 4,11 El principal diagnóstico diferencial del mesenquimoma fibrocartilaginoso es la displasia fibrocartilaginosa. Ambas lesiones presentan características clínicas, radiológicas e histopatológicas similares, e incluso algunos autores las consideran la misma entidad.…”
Section: Discussionunclassified
See 1 more Smart Citation